2005
DOI: 10.3748/wjg.v11.i47.7508
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve of laparoscopy-assisted distal gastrectomy with systemic lymphadenectomy for early gastric cancer

Abstract: Based on operative time analysis, this study show that experience of 50 cases of LADG with systemic lymphadenectomy for early gastric cancer is required to achieve optimum proficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
156
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(168 citation statements)
references
References 22 publications
9
156
1
2
Order By: Relevance
“…Reissman et al [22], in their study of 100 laparoscopic colorectal surgeries, stated that the learning curve and the types of procedures affected the morbidity rate. Kim et al [23], in their study of the learning curve for LADG, observed a result similar to the current finding: notable improvement in operating time after 50 surgeries. The notable finding of the current study was a considerable decrease in terms of operative time and development of complication until 50 cases had been managed, then a slight increase after 50 cases, followed by an another decrease and finally a plateau (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Reissman et al [22], in their study of 100 laparoscopic colorectal surgeries, stated that the learning curve and the types of procedures affected the morbidity rate. Kim et al [23], in their study of the learning curve for LADG, observed a result similar to the current finding: notable improvement in operating time after 50 surgeries. The notable finding of the current study was a considerable decrease in terms of operative time and development of complication until 50 cases had been managed, then a slight increase after 50 cases, followed by an another decrease and finally a plateau (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Several previous reports have suggested that LAG with lymph-node dissection may require at least 50-90 cases for a surgeon to gain competence [25][26][27]. It was reported that complications frequently occur during the introductory period, where the greatest of precaution must be taken [3,28].…”
Section: Discussionmentioning
confidence: 99%
“…There were no significant differences in hospital mortality. DFS in LTG was similar to that in OTG (HR, 0.62; 95% CI, 0.30, 1.27; P= 0.191) (Fig.2-3) [1][2][3][12][13][14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…In the past subtotal or total gastrectomy was always performed with open technique. In 1991 The Japanese school of gastric resection led by Professor Kitano performed the first Laparoscopic Subtotal Gastrectomy (LSG) for Early Gastric Cancer (EGC) [2][3][4][5][6][7][8]. Since this first reported surgery, Laparoscopic Gastrectomy (LG) has gained popularity in the last 20 years.…”
Section: Introductionmentioning
confidence: 99%